Umar ibn al-Khattab : the second of the four rightly-guided Caliphs - "Aziz,Maulvi Abdul" (Darussalam, Riyadh, 2012)
This volume is the second in Darussalam's "History of Islam" series, focusing on the era of the Rightly Guided Caliphs (Al-Khulafa ar-Rashidun). The book is structured into seven chapters, each highlighting significant aspects of Umar ibn al-Khattab's life and contributions